1995
DOI: 10.1128/jvi.69.4.2574-2582.1995
|View full text |Cite
|
Sign up to set email alerts
|

DNA vaccination against persistent viral infection

Abstract: This study shows that DNA vaccination can confer protection against a persistent viral infection by priming CD8 ؉ cytotoxic T lymphocytes (CTL). Adult BALB/c (H-2 d) mice were injected intramuscularly with a plasmid expressing the nucleoprotein (NP) gene of lymphocytic choriomeningitis virus (LCMV) under the control of the cytomegalovirus promoter. The LCMV NP contains the immunodominant CTL epitope (amino acids 118 to 126) recognized by mice of the H-2 d haplotype. After three injections with 200 g of NP DNA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(28 citation statements)
references
References 61 publications
1
25
0
2
Order By: Relevance
“…Another difference between the vaccines was the comparatively poor memory response to the N-GST protein and p-N DNA construct as compared to the p-hLAMP-N chimera construct. The limited efficacy of the conventional p-N DNA construct is consistent with many previous studies of our and other laboratories (Martins et al, 1995;Maecker et al, 1998;Oehen et al, 2000;Rush et al, 2002;Marques et al, 2003;Barros de Arruda et al, 2004). Although it is likely that there are multiple factors involved in memory T-cell differentiation (Masopust et al, 2004), we attribute the enhanced T-cell and memory responses to p-LAMP-N, at least in part, to the increased efficiency of trafficking of the LAMP-N chimera to the MHC II compartments of APCs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Another difference between the vaccines was the comparatively poor memory response to the N-GST protein and p-N DNA construct as compared to the p-hLAMP-N chimera construct. The limited efficacy of the conventional p-N DNA construct is consistent with many previous studies of our and other laboratories (Martins et al, 1995;Maecker et al, 1998;Oehen et al, 2000;Rush et al, 2002;Marques et al, 2003;Barros de Arruda et al, 2004). Although it is likely that there are multiple factors involved in memory T-cell differentiation (Masopust et al, 2004), we attribute the enhanced T-cell and memory responses to p-LAMP-N, at least in part, to the increased efficiency of trafficking of the LAMP-N chimera to the MHC II compartments of APCs.…”
Section: Discussionsupporting
confidence: 90%
“…Presentation of antigen epitopes and activation of CD4 T cells by MHC class II molecules are critical steps in generating memory B cell and CD8 + T-cell phenotypes (Wang and Livingstone, 2003;, and failure to elicit immune memory is one of the recognized problems of conventional genetic vaccines (Maecker et al, 1998). This defect may reflect an inadequate level of antigen expression or restricted access to the MHC II processing and presentation compartments by DNA-encoded endogenous antigens that lack a dedicated trafficking pathway (Martins et al, 1995;Maecker et al, 1998;Oehen et al, 2000;Rush et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Different isolates therapeutic approach has shown great utility for generating show considerable nucleotide sequence diversity, leading to a CTL response that not only protects against acute infection the subdivision of HCV genomes in at least six genotypes. 1 but also may have benefits in eradicating persistent viral In all genotypes, the viral RNA contains a large, open reading infection, 24,26,[28][29][30][31][32][33][34][35][36][37][38] of which HCV is an important human protoframe that encodes a polyprotein precursor of 3010 to 3033 type. Because the HCV core gene is highly conserved among amino acids.…”
Section: Growth Of Plasmacytomas Strong Ctl Activity Was Gen-mentioning
confidence: 99%
“…Finally, regarding the memory humoral response, it has been shown that mice vaccinated with DNA encoding an influenza viral HA antigen had levels of anti-HA antibodies comparable to or greater than those from convalescent sera of previously infected mice that persisted over 1 year (Martins et al, 1995;Torres et al, 1997). However, in other studies, plasmid DNA encoding a nucleoprotein of the LCMV virus administered intramuscularly failed to give appreciable antibody responses before viral challenge (Deck et al, 1997).…”
Section: A Humoral Responsementioning
confidence: 99%